2014
DOI: 10.1210/en.2014-1794
|View full text |Cite
|
Sign up to set email alerts
|

Male Bovine GH Transgenic Mice Have Decreased Adiposity With an Adipose Depot-Specific Increase in Immune Cell Populations

Abstract: White adipose tissue (WAT) is composed of mature adipocytes and a stromal vascular fraction (SVF), which contains a variety of cells, including immune cells that vary among the different WAT depots. Growth hormone (GH) impacts immune function and adiposity in an adipose depot-specific manner. However, its effects on WAT immune cell populations remain unstudied. Bovine GH transgenic (bGH) mice are commonly used to study the in vivo effects of GH. These giant mice have an excess of GH action, impaired glucose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 66 publications
6
39
0
Order By: Relevance
“…In humans, acromegaly leads to an increase in body water and lean body mass (Ikkos et al 1954, O'Sullivan et al 1994, Kamenický et al 2014, associated with a reduction in body fat (Freda et al 2008, Katznelson 2009. Similarly, giant bovine-GH transgenic mice (bGH) exhibit a lower body fat percentage, smaller WAT deposits and lower serum leptin levels (Berryman et al 2004, Benencia et al 2014. We found that Aip +/− mice exhibit a slightly enhanced total body weight at 3 and 7 months but not at 12 months of age.…”
Section: Discussionmentioning
confidence: 80%
“…In humans, acromegaly leads to an increase in body water and lean body mass (Ikkos et al 1954, O'Sullivan et al 1994, Kamenický et al 2014, associated with a reduction in body fat (Freda et al 2008, Katznelson 2009. Similarly, giant bovine-GH transgenic mice (bGH) exhibit a lower body fat percentage, smaller WAT deposits and lower serum leptin levels (Berryman et al 2004, Benencia et al 2014. We found that Aip +/− mice exhibit a slightly enhanced total body weight at 3 and 7 months but not at 12 months of age.…”
Section: Discussionmentioning
confidence: 80%
“…For example, we have evidence of significant alterations in ECM deposition with bGH mice having marked increases, specifically in the SubQ depot [143]. We also have preliminary data suggesting genotype and depot differences in gene or protein expression related to macrophage and T cell infiltration, angiogenic capacity, beige adipocyte composition, and glucose/lipid metabolism [179]. In fact, most of the unpublished data generated to explore the AT transcriptome in these mice reveal greater differences among depots, especially between SubQ and perigonadal, than among genotypes themselves [179].…”
Section: Obesity and Depot-specific Alterations In Gh Mouse Linesmentioning
confidence: 92%
“…We also have preliminary data suggesting genotype and depot differences in gene or protein expression related to macrophage and T cell infiltration, angiogenic capacity, beige adipocyte composition, and glucose/lipid metabolism [179]. In fact, most of the unpublished data generated to explore the AT transcriptome in these mice reveal greater differences among depots, especially between SubQ and perigonadal, than among genotypes themselves [179]. Clearly, the use of these lines may help unravel the underlying mechanism of how depot differences are established and maintained and provide insight into the novel means to modulate AT mass and obesity.…”
Section: Obesity and Depot-specific Alterations In Gh Mouse Linesmentioning
confidence: 95%
See 1 more Smart Citation
“…As expected, the overexpression of heterologous and homologous GH can lead to giant body with hyperplasia of thymus and spleen, and increased mitogenic response of spleen cells. But the giant mice exhibit a short lifespan and impaired glucose metabolism (Benencia et al 2014).…”
Section: Gh/igf-1 and Insulin/igf-1 Signalingmentioning
confidence: 99%